2012
DOI: 10.1016/j.rmed.2011.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence that GM-CSF inhalation improves lung clearance in pulmonary alveolar proteinosis

Abstract: GM-CSF inhalation decreased the concentration of total protein and SP-A in BALF, and increase interleukin-17 and cancer antigen-125 in improved lung of autoimmune pulmonary alveolar proteinosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…The 2-year-old LPI patient in their report had large amounts of cholesterol, cholesterol crystals and lipid-laden macrophages in the airways, and the authors suggested that therapies aiming to decrease the amount of cholesterol in the airways might be beneficial instead. On the other hand, in the study by Ohashi and colleagues, the GM-CSF inhalation therapy improved lung clearance and decreased the amount of protein in BAL fluid in a patient with autoimmune alveolar proteinosis (Ohashi et al 2012). Furthermore, in 2014, Yu and colleagues reported a patient with autoimmune PAP treated successfully with a combination of whole lung lavage and inhaled GM-CSF .…”
Section: Discussionmentioning
confidence: 99%
“…The 2-year-old LPI patient in their report had large amounts of cholesterol, cholesterol crystals and lipid-laden macrophages in the airways, and the authors suggested that therapies aiming to decrease the amount of cholesterol in the airways might be beneficial instead. On the other hand, in the study by Ohashi and colleagues, the GM-CSF inhalation therapy improved lung clearance and decreased the amount of protein in BAL fluid in a patient with autoimmune alveolar proteinosis (Ohashi et al 2012). Furthermore, in 2014, Yu and colleagues reported a patient with autoimmune PAP treated successfully with a combination of whole lung lavage and inhaled GM-CSF .…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have examined the efficacy of either inhaled or subcutaneous GM-CSF in patients with PAP with anti-GM-CSF antibodies. [565][566][567] Therapy does not seem to affect autoantibody titers, and both routes of administration were effective, possibly by complexing with (consuming) the autoantibody. Long-term administration appears to be both effective and safe.…”
Section: Defects Of the Respiratory Burst Chronic Granulomatous Disementioning
confidence: 99%
“…In cases of acquired PAP, definitive treatment rests on addressing the underlying disorder or avoiding the suspected environmental agent (1). Recently, studies have demonstrated that GM-CSF (inhalation or subcutaneous) can result in improvement in some patients with idiopathic PAP (12,13). Other options focus on reducing the amount of autoantibodies via B-cell depletion therapy (rituximab) or removal of autoantibodies (plasmapheresis); however, the exact role of these modalities remains to be defined (14,15).…”
Section: Abstract: Alveolar Infiltrates; Crazy Paving; Gm-csf; Pulmomentioning
confidence: 99%